Perancangan Aplikasi Marketplace Jasa Percetakan Berbasis Website - Rahmat Fauzi; Satrio Wibowo; Dela Youlina Putri (Fountain of Informatics Journal, 2018)
The development of e-commerce based on marketplace is very familiar in Indonesia. However, there is no digital printing services based on marketplace whereas the need of these services remains high. Currently, the printing house services based on business to customer (B2C) style so people have to compare the pricing and service information directly to print owners both online and offline. One solution to face this problem is to create a marketplace printing services called CETAKIN. By this application, information of printing service in a region can be integrated into this system. This system of printing marketplace integration is built with waterfall method with four stages namely needs analysis, system design, implementation, and system testing with PHP programming language and MySQL Database. The features that exist in this marketplace application is registration, search, order printing services. This information system application provides added value that makes the process of printing search and printing service prices more effective and efficient because people do not need to visit the address of printing. On the other hand, the benefits gained for the store owner can expand the coverage of his store's advertising so that the public know more  the existence of the printing.